Elevated Plasma Melatonin Levels Are Correlated With the Non-motor Symptoms in Parkinson’s Disease: A Cross-Sectional Study - Li, Linyi; Zhao, Zhenxiang; Ma, Jianjun; Zheng, Jinhua; Huang, Shen; Hu, Shiyu; Gu, Qi; Chen, Siyuan (Frontiers in Neuroscience, 2020)
Background: Melatonin is the major hormone produced and secreted at night by the pineal gland into the cerebrospinal fluid (CSF) and circulation. The relationship between plasma melatonin levels and Parkinson's disease is not clear. The aim of the current study was to assess plasma melatonin levels in Parkinson’s disease (PD) patients and to examine the effects of melatonin on nonmotor symptoms. Methods: In this cross-sectional study, we evaluated 61 patients with idiopathic PD (males n = 30 (49.2%), average age 62.4 years (range: 46-73 years)) and a total of 58 healthy volunteers (males n = 30 (51.7%), average age 64.3 years (range: 45-70 years)) who participated in the study. Plasma melatonin levels were measured using an enzyme-linked immunosorbent assay. The severity of disease in PD patients was scored by the Unified Parkinson’s Disease Rating Scale and the Hoehn and Yahr Staging scale. The quality of life in PD patients was assessed by the 39-item Parkinson’s Disease Questionnaire. The nonmotor symptoms were assessed by the 14-item Hamilton Anxiety Rating Scale, the 24-item Hamilton Depression Rating Scale, the Parkinson Disease Sleep Scale, the Epworth Sleepiness Scale and the Non-Motor Symptoms Scale for PD. Results: Compared with the healthy controls, the plasma melatonin levels were significantly higher in PD patients (12.82±4.85 vs. 19.40±4.23, p<0.001). Plasma melatonin levels were significantly associated with the levodopa equivalent daily dose and nonmotor symptoms such as sleep disorders, cardiovascular symptoms, and gastrointestinal symptoms. Conclusion: This study revealed that the plasma melatonin levels in PD patients were significantly higher than those in healthy controls. This finding suggested a potential underlying link between plasma melatonin levels and the nonmotor symptoms in PD patients.